PERFORMANCE THROUGH EFFICIENCY IN THE PUBLIC HEALTHCARE SYSTEM - A DEA APPROACH IN AN EMERGENT COUNTRY - NISTOR, Cristina Silvia; ȘTEFĂNESCU, Cristina Alexandrina; SÎNTEJUDEANU, Mara Andreea; CRIȘAN, Andrei-Răzvan (Studia Universitatis Babeș-Bolyai Oeconomica, 2017)
https://doi.org/10.1515/subboec-2017-0003 Aiming to analyze the efficiency of the public sector, this paper enriches the literature by providing insights of the healthcare system for an emergent country – Romania. The empirical findings reached by applying the input orientated-variable return to scale (VRS) model of Data Envelopment Analysis (DEA) and Tobit regression method are determined on two key levels of the study. The Data Envelopment Analysis technique quantifies the efficiency within 20 representative hospitals located in the four administrative macro-regions, highlighting the ways of increasing efficiency, while the Tobit regression identifies the factors that influence the efficiency level. The results of the investigation allow for comparisons with other emerging countries, as efficiency has become an increasingly significant factor for public sector evolution. JEL classification: H41, I18, M40